Understanding sexuality from the security gospel perspective: Mountain of Fire and Miracles Ministries as a case study - Adelakun, Adewale (HTS teologiese studies, 2017)
This article examines a new dimension in the Nigerian Pentecostal understanding of sexuality, which is influenced by the security gospel emanating from Mountain of Fire and Miracles Ministries in Nigeria. This new dimension is noted in how Mountain of Fire and Miracles Ministries intricately connects sexuality with destiny. This article shows how Mountain of Fire and Miracles Ministries promotes a conservative understanding of sexuality as the key to securing believers’ destinies. Understanding sexuality from the security gospel perspective is an indication that the Pentecostal theology of sex is dynamic and ambivalent, especially when the theology is spiced with African traditional beliefs. This is demonstrated through a content analysis of the teachings and messages of Pastor Daniel Olukoya, the founder of Mountain of Fire and Miracles Ministries, which are available in print, audio and video clips. It is argued that the persuasive manner in which these teachings are presented tends to create a phobia of sex in the minds of listeners.